Comparison of Sports Performance and Kinanthropometric Profiles of Elite Female Basketball and Volleyball Players over the Course of a Competitive Season - Miguel Ortega, Álvaro; Calleja González, Julio; Mielgo Ayuso, Juan (My University, 2023)
In order to maximize sports performance of team sportswomen, knowledge of the player¿s characteristics in terms of different aspects and at different times of the season is needed. While the anthropometric and physical characteristics of men¿s sports teams have been extensively studied, research on women¿s basketball and volleyball is scarce. (1) Purpose: This study aims to contribute data about the anthropometric and physical characteristics of female basketball and volleyball players from elite women¿s teams (age: 24.3 ± 2.7 years; playing experience: 14.825 ± 2.8 years) (n = 23) with a two-fold objective: (1) to describe and compare the anthropo metric characteristics of these two disciplines; and (2) to identify possible differences in various parameters of sports performance depending on the discipline. (2) Methods: The anthropometric profile includes the measurements recommended by the International Society for the Advancement of Kinanthropometry; the performance tests described aerobic and anaerobic power exercises. (3) Results: The overall somatotype of the players was moderate mesomorphic and low endo morphic (5.107¿3.046¿1.883). Statistical differences were found between the improvement of the physical performance level of female basketball players (77%) and female volleyball players (10%) from the first to the last measurement, with better results in most of the performance tests (p < 0.05). The sum of skinfolds was higher in female basketball players (p > 0.05). The percentage of fat-free mass correlated with improvements in lower body strength. (4) Conclusion: Lean body mass is an important predictor of exercise performance intensity. Excess fat mass is detrimental to the development of strength and endurance. Keywords: kinanthropometry; basketball; volleyball; performance; women